Effectiveness of Legal Supervision by the Malang City Communication and Information Office on Phishing: A Perspective of the ITE Law and Maqāṣid al-Sharīʿah - Al Munawar, Faishal Agil; Zahro, Maulida (PT. Riset Press International, 2025)
Phishing refers to online fraud activities that deceive victims into disclosing their data, leading to various risks such as misuse of banking accounts, email accounts, and social media. This study is based on the increasing number of phishing cases in society, including among university students, which have resulted in financial losses and personal data breaches, thereby violating Law Number 1 of 2024 concerning Electronic Information and Transactions (ITE Law). Therefore, local government supervision is deemed necessary to address phishing activities occurring in Malang City. The objective of this study is to analyze the effectiveness and challenges of the supervision carried out by the Department of Communication and Information (Diskominfo) of Malang City on phishing, from the perspective of the ITE Law and Maqāṣid al-Sharīʿah. The research employs an empirical juridical method with a socio-juridical approach. The findings indicate that the supervision efforts by Diskominfo Malang include public education on the dangers of phishing and prevention strategies, provision of a reporting channel called “Malangkota-CSIRT,” and coordination with relevant stakeholders. From the perspective of Maqāṣid al-Sharīʿah, these efforts aim to realize public benefit (maslahah) by protecting wealth (hifzh al-mal) and life (hifzh al-nafs). However, the effectiveness of these supervision efforts remains limited due to legal constraints within the ITE Law and several practical challenges, such as unequal dissemination of information, limited human resources and budget, and inadequate infrastructure, all of which hinder the supervision and response process.